Spawning and developmental biology of endangered Pabdah catfish, Ompok pabda (Hamilton, 1822) - Tumpa, Israt Jahan; Hossain, Md Saddam; Uddin, Md Nagim; Hossain, Zakir (Asian Journal of Medical and Biological Research, 2020)
Pabdah catfish, Ompokpabdawas collected from the Old Brahmaputra river and successfully induced to breed by injecting pituitary gland extract to evaluate spawning performances and developmental stages under a photo microscope from February 2018 to August 2018. In this study, absolute fecundity of the O. pabdafemales varied from 6,676 to 20,410 eggs per fish. The GSI value of male and female was lower during September and gradually attained its maximum level in June with the highest average value 6.75±0.2 and 1.053±0.2 in female and male, respectively. The average fertilization and hatching rate of eggs were found 78.67±1.33% and 70.21±0.73%, respectively at 24.5±1.0°C. Fertilized eggs were brownish in color, very transparent and adhesive in nature with 1.0 to 1.2 mm in diameter. Cleavage stages were completed at 1.50 h of post fertilization and it eventually took 23.00 h for hatching. Larva was appeared with prominent three pairs of barbells after 12.00 h of hatching. It took 3 d post hatching to absorb their yolk sac and feeding exogenously. The present work supplemented to the deficient information on detailed spawning and developmental biology of O. pabdain order to save this species from extinction. Asian J. Med. Biol. Res. September 2020, 6(3): 449-459